Implementation of National Education Standards Policy at State Middle School 1 Mentarang, Mentarang District, Malinau Regency - henry, Henry; Hafel, Muhlis; Darmanto, Darmanto (Enrichment: Journal of Multidisciplinary Research and Development, 2025)
The implementation of the National Education Standards (SNP) policy is the application of policies related to minimum criteria on relevant aspects to support the implementation of the national education system and must be met by organizers and/or educational units throughout the jurisdiction of the Unitary State of the Republic of Indonesia. The function of the National Education Standards is as a basis for education management which includes planning, implementation, and supervision of education in order to achieve the expected goals, namely the realization of quality education. While the purpose of the National Education Standards is to measure, evaluate, and assess the quality of education, the results of which will be a reference for compiling a program to improve the quality of education based on regional characteristics in each educational unit. This study aims to describe the implementation of the National Education Standards policy and the factors that influence the implementation of the National Education Standards policy at SMP Negeri 1 Mentarang, Mentarang District, Malinau Regency. The design of this study uses a descriptive research type with a qualitative approach. By describing or depicting the state of the research object at the present time, based on the facts that appear or as they are. Sources of information on places and informants have been selected based on certain considerations and taken based on research objectives. The informants in this study consisted of schools as implementers in the field, school committees, and students as target groups for the implementation of the National Education Standards policy as well as the Malinau Regency Education Office and School Supervisors as leading sectors that communicate, mobilize, and encourage the implementation of the National Education Standards policy and the Education Council as observers of education. Overall, the implementation of the National Education Standards policy at SMP Negeri 1 Mentarang has been fulfilled and can be seen from the data obtained. The results of the study indicate that the four factors that are the model for implementing public policy, namely communication, resources, disposition (attitudes), and organizational/bureaucratic structure have been implemented well as an effort to fulfill the National Education Standards policy at SMP Negeri 1 Mentarang, but need to be optimized, because these four factors can be obstacles to the implementation of the National Education Standards policy at SMP Negeri 1 Mentarang.